This is not about us [large type] - Goodman, Allegra (Random House Large Print, 2026)
"Was this just a brief skirmish, or the beginning of a thirty-year feud? In the Rubenstein family, it could go either way. When theirbeloved [younger] sister passes away, Sylvia and Helen Rubinstein are unmoored. A misunderstanding about apple cake turns into decades of stubborn silence. Busy with their own lives--divorces, dating, career setbacks, college applications, bat mitzvahs, and ballet recitals--their children do not want to get involved. As for their grandchildren? Impossible"--Publisher description.